Strategic for Improving Teacher Information Literacy as an Effort to Develop Professionalism in the Digital Era - Yuslimah, Anisa Isti; Achmad, Dedy; Nurdin, Nurdin (Universitas Ahmad Dahlan, 2025)
Background/purpose. The integration of digital systems in teacher performance management, such as Ruang GTK, demands adequate digital literacy among teachers. However, many educators face challenges in effectively utilizing the platform due to varying levels of competence and institutional support. This study aims to examine how teachers’ digital literacy is strategically managed within a school setting to enhance the use of Ruang GTK as a tool for professional performance. Materials/methods. A qualitative approach with a single case study method was employed at SMPN 5 Bandung. Eight purposively selected teachers participated in semi-structured interviews, direct observations, and document analysis. Thematic analysis was conducted to identify patterns, and SWOT–TOWS analysis was used to formulate strategic responses. Results. Findings reveal inconsistent levels of digital literacy among teachers, with younger educators adapting more quickly than their senior counterparts. Ruang GTK is primarily used for administrative reporting, while developmental features remain underutilized. Identified challenges include lack of technical support, limited training, and low engagement with digital tools. From the analysis, four strategic approaches were developed: empowering digital champions, implementing continuous peer coaching, establishing a digital literacy task force, and embedding digital competence in performance indicators. Conclusion. Strategic management of digital literacy is essential to optimize the use of Ruang GTK in enhancing teacher performance. Schools must foster a collaborative and reflective digital culture supported by ongoing capacity building and institutional commitment.